Stable Sunspot Equilibria in a Cash-in-Advance Economy - George W. Evans; Seppo Honkapohja; Ramon Marimon (Center for Economic Studies and ifo Institute (CESifo), 2001)
We develop a monetary model with flexible supply of labor, cash in advance constraints and government spending financed by seignorage. This model has two regimes. One regime is conventional with two steady states. The other regime has a unique steady state which can be determinate or indeterminate. In the latter case there exist sunspot equilibria which are stable under adaptive learning, taking the form of noisy finite state Markov processes at resonant frequencies. For a range of parameter values, a sufficient reduction in government purchases will eliminate these equilibria.
Keywords: 330; indeterminacy; learnability; expectational stability; endogenous fluctuations; seignorage